Balancing legume-cereal proportions in cover crop mixtures to minimize N2O emissions - Guillermo Guardia; Diego Abalos; Emanuele Ribatti; Federico Ardenti; Federico Capra; Giacomo Mortella; Vincenzo Tabaglio; Miguel Ángel Ibáñez; Ji Chen; Andrea Fiorini (Geoderma)
Legume-cereal cover crop mixtures offer a promising approach to reduce nitrate leaching and enhancing soil fertility. However, the impacts of these mixtures on N2O emissions during both the cover cropping and post-incorporation phases, as well as the relative contribution of roots and shoots to N2O emission, remain uncertain. To address these knowledge gaps, we conducted a two-phase greenhouse experiment. In the first phase, cover crops were grown encompassing six treatments: control (no cover crop), pure vetch (Vicia villosa Roth), pure rye (Secale cereale L.), and mixtures with 33 %, 50 % and 66 % of the pure rye sowing rate paired with 66 %, 50 % and 33 % of the pure vetch sowing rate, respectively. In the second phase, focusing on the post-incorporation effects, the same treatments were arranged in mesocosms with both roots and shoots, and in mesocosms with roots only. During the first phase, the proportion of fine/very fine roots and root length density were negatively correlated with mineral N content and N2O emissions. Mixing rye with vetch increased total dry biomass and N yield for all mixtures compared to rye alone. In mixtures, the proportion of fine roots, root length density, and the root C:N ratio decreased compared to rye. Most of the N2O emissions occurred after cover crop incorporation, with roots contributing more (average 57 %) than shoots (average 31 %). Total N2O emissions increased with increasing proportion of vetch, but the mixture with 33 % vetch and 66 % rye maintained N2O emissions as low as rye monoculture. Our study indicates that adjusting the seed proportion in legume-cereal mixtures serves as an effective tool to balance the benefits of pure legume (increased total biomass, and C and N yields) and pure cereal (decreased N2O emissions and soil mineral N pool) cover cropping.